(untitled) (Tanzania Medical Journal, 2015)
ntroduction: The subject of postoperative complication and prevention has continued to generate interest in the last decade. Unfortunately, very few data are available locally to assess the extent of problems and measures designed to address them. This study was designed to identify immediate post-operative complications and associated factors in patients admitted at operation theatre recovery rooms of Muhimbili National Hospital, Dar es Salaam, Tanzania.Methods: A prospective study was conducted over a six-month period from July 2007 to January 2008 on patients who underwent various types of surgical operations under regional or general anaesthesia admitted to these recovery rooms. Complications were documented according to predefined criteria and were critically evaluated.Results: Out of total of 265 patients recruited, 87.5% had some form of complication. Pain was the commonest complication occurring in 40.8% patients. 37.0% patients had complications referable to the respiratory system, 30.6% patients each had abnormal cardiovascular parameters and shivering, 26.0% patients had hypothermia, 9.8% patients had nausea and/or vomiting, 6.0% patients presented with restlessness, 5.3% patients presented with abnormalities referable to central nervous system and 1.6%patients presented with other problems. Many patients had more than one complication.Conclusions: This study has shown that despite of recent advances in anaesthetic techniques and the introduction of newer anaesthetic drugs, the incidence of post anaesthetic complications is high in our environment. Therefore a large study is needed to know exact incidence of complications in these patients.